2022
DOI: 10.2147/jmdh.s362625
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Length of Stay and Related Factors for COVID-19 Inpatients Among the Four Southern Regions Under the Proposed Southern Business Unit of Saudi Arabia

Abstract: Objective To assess the length of stay (LoS) variation for COVID-19 inpatients among the four regions of the Southern Business Unit (SBU). Methods This is a comparative retrospective study of the LoS of COVID-19 inpatients in the four regions of the SBU in the KSA. Data was collected from the Ministry of Health (MoH) in all hospitals in the SBU. Participants were all patients admitted with confirmed COVID-19 between March 2020 and February 2021. Variables included regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Similar studies elsewhere also identified diabetes mellitus (23.6%), hypertension (22.5%), and cardiovascular disease (3.7%) as common comorbidities in COVID-19 patients (Alimohamadi et al, 2022). However, comparative retrospective studies in Saudi Arabia have shown that comorbidities had no statistically significant correlation with LoS (Alharbi et al, 2022). The study also showed that important clinical biomarkers in COVID-19 patients included creatinine, D-dimer, NT-proBNP and TropT.…”
Section: Discussionsupporting
confidence: 56%
“…Similar studies elsewhere also identified diabetes mellitus (23.6%), hypertension (22.5%), and cardiovascular disease (3.7%) as common comorbidities in COVID-19 patients (Alimohamadi et al, 2022). However, comparative retrospective studies in Saudi Arabia have shown that comorbidities had no statistically significant correlation with LoS (Alharbi et al, 2022). The study also showed that important clinical biomarkers in COVID-19 patients included creatinine, D-dimer, NT-proBNP and TropT.…”
Section: Discussionsupporting
confidence: 56%
“…Considering that the outcome in this analysis was the overall LOS, further analyses of the more detailed KPIs collected through the Ada'a program, namely, door to doctor, doctor to decision, and decision to disposition, in addition to this overall KPI, will provide the necessary information to develop tools/policies for improvement. We also recommend measuring ED LOS at the cluster level of the business units, as proposed by the new model of care introduced in the healthcare transformation plan of Vision 2030, and at the regional level of the 13 administrative regions of Saudi Arabia (55,56). With highly varying socioeconomic levels among regions, we expected to find regional differences due to these variations.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the present study also suggested that the average length of stay upon admission was 6 days (range: 1-68) for inpatients due to a positive COVID-19 test. The average length of stay in studies in Brazil and Saudi Arabia was 10 ± 8 (33) and 10 days, respectively (37). Another study reported the length of hospital stay for deadly cases in the USA, Italy, and Germany was 2-10, 1-6, and 5-19 days, respectively (38).…”
Section: Discussionmentioning
confidence: 99%